2022
DOI: 10.1021/acsorginorgau.2c00019
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Stereoconvergent Synthesis of Homochiral β-CF3, β-SCF3, and β-OCF3 Benzylic Alcohols

Abstract: We describe an efficient catalytic strategy for enantio- and diastereoselective synthesis of homochiral β-CF3, β-SCF3, and β-OCF3 benzylic alcohols. The approach is based on dynamic kinetic resolution (DKR) with Noyori–Ikariya asymmetric transfer hydrogenation leading to simultaneous construction of two contiguous stereogenic centers with up to 99.9% ee, up to 99.9:0.1 dr, and up to 99% isolated yield. The origin of the stereoselectivity and racemization mechanism of DKR is rationalized by density functional t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…Homochiral fluorinated alcohols, which are considered to be emerging structural motifs in medicinal chemistry (Cotman, 2021), can be obtained in high yields employing dynamic kinetic resolution (DKR) with Noyori-Ikariya asymmetric transfer hydrogenation (ATH) (Betancourt et al, 2021;Cotman et al 2022;Molina Betancourt et al, 2022). When Ru II -catalyzed DKR-ATH was applied to CF 3 CO-substituted benzofused cyclic ketones, it was observed that single or double reduction occurs, yielding either diastereo-and enantiopure monoalcohols or 1,3-diols (Cotman et al, 2016).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Homochiral fluorinated alcohols, which are considered to be emerging structural motifs in medicinal chemistry (Cotman, 2021), can be obtained in high yields employing dynamic kinetic resolution (DKR) with Noyori-Ikariya asymmetric transfer hydrogenation (ATH) (Betancourt et al, 2021;Cotman et al 2022;Molina Betancourt et al, 2022). When Ru II -catalyzed DKR-ATH was applied to CF 3 CO-substituted benzofused cyclic ketones, it was observed that single or double reduction occurs, yielding either diastereo-and enantiopure monoalcohols or 1,3-diols (Cotman et al, 2016).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Dynamic kinetic resolution (DKR) based on Ru II -catalyzed Noyori-Ikariya asymmetric transfer hydrogenation (ATH) has proven to be a highly efficient strategy for the stereoconvergent synthesis of secondary alcohols (Cotman, 2021). The commercial availability of a wide range of Ru II catalysts, comparatively mild reaction conditions, and the ability to use racemic mixtures of ketones as starting materials make this approach particularly attractive for the synthesis of -substituted benzyl alcohols, which have been shown to be valuable building blocks for pharmaceuticals and can crystallize as homochiral single-component mechanically responsive crystals that exhibit elastic or plastic flexibility (Cotman et al, 2019(Cotman et al, , 2022. When ATH of non-symmetric CF 3 -substituted 1,3diketones was attempted, it was found that two consecutive DKR-ATH reactions can occur and that diastereo-and enantiopure 1,3-diols can be obtained in a one-pot process (Cotman et al, 2016).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…In most cases, the ketone groups adjacent to the stereochemically labile carbon centers are reduced. In this context, a large number of racemic ketones such as α-substituted cyclic ketones, acyclic ketones bearing α-electron-withdrawing groups (EWGs), α-ketoesters bearing β-labile stereocenters, and so forth, have been exploited to undergo efficient ATH-DKR to afford a variety of enantioenriched secondary alcohols with adjacent stereocenters . The great value of such processes has been witnessed in the synthesis of various pharmaceuticals, fine chemicals, agrochemicals, flavors, and so forth, by a plethora of companies .…”
Section: Introductionmentioning
confidence: 99%